Building virtual rapport with emotion expressions: hotel responses to positive online reviews - Ly, Wen Taw; Libert, Alan R.; Paramasivam, Shamala (Language Institute, Thammasat University, 2022)
The rapid digital revolution in recent decades has transformed conventional Word-of-Mouth (WOM) into electronic WOM (eWOM). The significance of digital emotion in eWOM has been widely recognized due to its influential effect on consumer trust. There is increasing research on digital emotion contagion, which refers to exposure to emotions on digital platforms, which evokes internet users’ emotions. Drawing on Spencer-Oatey’s (2008) Rapport Management Model (RMM), this study investigates the stylistic domain of RMM, focusing on the affective lexical resources that express emotions used by Malaysian hotels when responding to positive online reviews on TripAdvisor. These affective lexical resources were analyzed using Martin and White’s (2005) Appraisal Theory. The findings demonstrated that the five- and four-star hotels had higher frequencies of affective lexical variation than did the three-star hotels. From the perspective of RMM, the affective lexical choices used by the high-end Malaysian hotels appeared to reflect the cultural values of gratitude and respect in Asian hospitality in fostering virtual emotional connections with reviewers. This study enriches the work on English for Specific Purposes (ESP) course design as digitally engaging via online business communication should be an integral part of business-related ESP courses.